Effect of postural correction on dyspnea index and pulmonary functions in chronic obstructive pulmonary disease patients - ARCHANA SING,; G.D.VISHNU VARDHAN, (International Journal of Pharma and Bio Sciences, 2017)
To study the effectiveness of postural correction on dyspnea index and pulmonary functions in COPD patients, 30 subjects of age group 40-70 years were included according to GOLD criteria having MILD (FEV1/FVC < 0.70, FEV1 > 80% predicted), MODEARTE (FEV1/FVC < 0.70, 50% < FEV1 < 80% predicted) and SEVERE (FEV1/FVC < 0.70, 30% < FEV1 < 50% predicted). They were divided into two groups for two different treatments selected by chit method into their respective GROUP 1 and 2. GROUP 1 patients were given pursed lip breathing and GROUP 2 patients were given postural correction along with pursed lip breathing. Pre and Post PFT, ISD, Borg Score and 6MWTD were taken as outcome measures, were compared and the results showed the effectiveness of postural correction.